2003
DOI: 10.1034/j.1399-0012.2003.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for early mortality following liver transplantation

Abstract: Pre-LT renal insufficiency is the most significant risk factor for early mortality and suggests that LT should be performed before evidence of irreversible renal insufficiency becomes manifest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 35 publications
(43 reference statements)
1
57
0
1
Order By: Relevance
“…These variables are consistent with the findings in other cohorts (5,7,10,14,15,20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). As for RD certain malignancies (HCC beyond Milan (35) and advanced cholangiocarcinomas (36)) are no longer indications for LT.…”
Section: Discussionsupporting
confidence: 88%
“…These variables are consistent with the findings in other cohorts (5,7,10,14,15,20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). As for RD certain malignancies (HCC beyond Milan (35) and advanced cholangiocarcinomas (36)) are no longer indications for LT.…”
Section: Discussionsupporting
confidence: 88%
“…Many authors have reported models for predicting postliver transplantation survival and these models are mostly influenced by pretransplant recipient factors such as chronic renal failure, recipient age and body mass index (18)(19)(20). These factors are mostly unrelated to the direct complications of cirrhosis and are more related to the general state of health of the individual recipient.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of previous relatively small observational studies had demonstrated a correlation between recipient hyponatremia and post-transplant mortality [28,29,30]. However, an equivalent number of similar quality studies have challenged this notion [31,32,33].…”
Section: Impact Of Hyponatremia On Post-transplant Outcomesmentioning
confidence: 99%